2008
DOI: 10.1097/ico.0b013e318165b1cd
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Extracellular Matrix Components and Proteinases in Human Corneal Buttons With INTACS for Post-Laser In Situ Keratomileusis Keratectasia and Keratoconus

Abstract: Purpose-To perform an immunohistochemical evaluation of corneas with INTACS for post-laser in situ keratomileusis (LASIK) keratectasia and keratoconus, obtained after corneal transplantation.Methods-Corneas from 1 patient with INTACS for post-LASIK keratectasia and 2 patients with INTACS for keratoconus were obtained within 3 hours after penetrating keratoplasty, and cryostat sections were analyzed by immunostaining for 35 extracellular matrix (ECM) components and proteinases.Results-In the stroma of all corne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 42 publications
5
27
0
2
Order By: Relevance
“…That suggests that the ICRS promote indirectly a kind of reorganization by collagen lamellas of corneal stroma contributing for better values of keratometry, asphericity and visual acuity, which raises the possibility of corneal shrinkage after the procedure. Such a presumption is corroborated based on other studies that demonstrated the formation of collagen and other extracellular matrix components 21 after ICRS implantation.…”
Section: Discussionsupporting
confidence: 71%
“…That suggests that the ICRS promote indirectly a kind of reorganization by collagen lamellas of corneal stroma contributing for better values of keratometry, asphericity and visual acuity, which raises the possibility of corneal shrinkage after the procedure. Such a presumption is corroborated based on other studies that demonstrated the formation of collagen and other extracellular matrix components 21 after ICRS implantation.…”
Section: Discussionsupporting
confidence: 71%
“…Some histological studies of human corneas that were removed for keratoplasty due to ICRS complications or refractive failure have been reported. However, these studies do not established a temporal sequence of events, and the number of eyes analyzed was small [27,28]. For these reasons we thought it was necessary to develop an experimental animal model to study clinical, optical, and histological events together throughout the wound healing process after Ferrara ICRS implantation in good and complicated eyes.…”
Section: Discussionmentioning
confidence: 99%
“…However, these techniques are not able to describe the cellular events of corneal wound healing around the implanted segments. The histological studies in human corneas were performed on corneas explanted for keratoplasty at different time points, but no temporal sequence of events was established, and the number of eyes analyzed was generally very small [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological studies in animals have been performed in rabbits [17] and hens [22]. However, there are relatively few studies that have reported the complete histological changes that occur during the wound healing process of both human and animal corneas [17,18,20,21]. These studies included only a small number of eyes and did not show the evolution of the process over a sufficient amount of time, especially soon after surgery, to document all of the changes that take place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation